Farmacoterapia e fatores associados à adesão ao tratamento em idosos com síndrome metabólica - GOMES, Nayara Cândida (2015)
The Metabolic Syndrome (MS) needs special attention because of its complications and the huge impact on morbidity and mortality. The objective was to describe the sociodemographic, biochemical, clinical and anthropometric characteristics of elderly patients diagnosed with MS, accompanied by the MS clinic in Federal University of Triangulo Mineiro; identify the prevalence of drug treatment adhesion, and physical activity as a component of non-medication treatment of the elderly; determine the value of the Food Guide 10 Steps to a healthy diet for elderly people; check the most prevalent International Diabetes Federation’s MS diagnostic criteria among elderly people; describe pharmacotherapy and possible drug interactions of elderly people with MS; identify adhesion factors in pharmacological and nonpharmacological treatments to MS in elderly patients. Quantitative, analytical and cross-sectional study of 263 elderly patients with MS living in Uberaba-MG. Instruments used: Mini Mental State Examination, Brazilian Multidimensional Functional Assessment Questionnaire, Geriatric Depression Scale abbreviated, Katz Index, Lawton and Brody Scale, Medication Regimen Complexity Index, Questionnaire to Evaluate Attitudes Towards Taking Medicines, Brief Medical Questionnaire, International Physical Activity Questionnaire (version adapted for the elderly), Healthy Eating for Senior Citizens in 10 Steps Food Guide, Drug-Reax Micromedex®, updated version of the Beers criteria. We proceeded to the analysis with the chi-square test and multiple logistic regression model (p<0,05). Female elderly predominated (70,7%); age 60|-70 years (51,7%); They lived with husband (or wife) (63,9%); had 1|-4 years of education (49,0%); income ≤ 1 minimum wage (62,4%); eutrophic (49,6%) and with total cholesterol levels (76,4%), low density lipoprotein cholesterol (66,5%), ferritin (79,1%), C-reactive protein (93,5%) and uric acid (80.2%) within the normal range; they were independent for basic activities of daily living (51,0%); and dependent for instrumental activities of daily living (99,2%); with health self-perception positive (50,2%); five or more morbidity conditions (89,7%); with absence of depressive symptoms (81,7%); low adherence to drug treatment (51,0%) and inactive for the practice of physical activity (52,5%). The step in good food intake most often seen was not to add salt to already prepared food (91,6%). The most frequent MS component was abnormal fasting glucose (91,6%). Most had polypharmacy (73,0%), proceeded in a positive way facing the use of medications (62,7%), used potentially inappropriate medications (54,4%), and had possible drug interactions (75,3%). Treatment adherence was associated with owning income >1 minimum wage (p=0,023), living together (p=0,013), drug interactions absence (p=0,016) and positive self-perception of health (p<0,001). Factors that increased adherence to physical activity practice: living with a partner (p=0,021), absence of depressive symptoms (p=0,020), positive self-perception of health (p=0,005) and functional capacity for basic activities of daily living (p=0,007). Conclusion: factors associated with adherence to treatment of MS, observed in this study, help on planning public health efforts aiming the prevention of complications.